Advances in the Emotive Analysis of People when Consuming Alcoholic Drinks through a Brain-Computer Interface - Luz Moreno, César Peña, Holger Cacua, Luis Peña, Jorge Araque (International Journal of Advanced Science and Technology, 2020)
This article presents the development of pilot tests that allow a quantitative analysis of the emotions of a group of users, carrying out an activity that requires considerable attention. The activities are carried out in rounds where the consumption of alcoholic beverages differentiates them. Neuro signals are recorded using a 5-channel brain-computer interface. The results allowed to show that excitement is one of the most relevant emotions in the incidence of users behavior while performing the activity. However, it could be concluded that it is possible to create an equation that relates several emotions simultaneously, as well as the intake of alcoholic beverages, obtaining a better correlation with the score of the activities proposed in the experiments. The development of this equation was proposed employing an optimization technique called particle swarm, which was conceived to model social behaviors. Keywords: Brain-Computer Interface, EEG, Emotions, Neuro signs, Alcoholic Beverages